Structure-actvity relationship of nitric oxide synthase inhibitors: a theoretical approach - Morales, Elba Mirta (2002)
Nitric oxide (NO) has become an important intracellular and intercellular signal molecule and inhibition of the enzyme which produces NO (NOS, NO synthase) become a major goal for pharmacological researchers. We performed a complete search for the lowest-energy conformations at the AM1 calculation level, for zwitter-ionic species of NOS inhibitors, analogs to L-Arg. The lowest- energy conformations obtained were fully optimized at the ab initio theory levels: HF/3-21G and HF/6-31G*. L-NNA, L-NMA and L-CPA exhibited a conformational behavior quite comparable to that of L-Arg. L-NIL, L-NIO and L-NAME achieved to completely different conformations when compared to L-Arg, L-NIL, highly selective for the inducible isoform of NOS, exhibited conformational as well as charge distribution differences compared to L-Arg. L-NAME and L-NNA are highly selective compounds for the constitutive isoforms. Both compounds share the chain lengths of L-Arg and bear a nitro-substituent over the guanidinium group, which causes changes on the net atomic charges of the N-guanidinium atoms. Moreover, differences were observed on net atomic charges and density distribution analyzed by means of molecular electrostatic potentials (MEPs). These differences might be of great importance at determining the selectivity of the different inhibitors. On the basis of the conformational and molecular properties of the different NOS inhibitors and the selectivity of the analogs studied, we propose the requirements for the different NOS isoforms.